Stress Hyperglycemia and Outcome of Non-diabetic Patients After Acute Ischemic Stroke - Zhu, Bihong; Pan, Yuesong; Jing, Jing; Meng, Xia; Zhao, Xingquan; Liu, Liping; Wang, Yilong; Wang, Yongjun; Wang, Zhimin (Frontiers in Neurology, 2019)
Background and purpose Stress hyperglycemia is relative hyperglycemia after suffering an acute illness such as stroke, even without preexisting diabetes. Our study aimed to determine the relationship between stress hyperglycemia and outcome of nondiabetic patients with acute ischemic stroke. Methods Patients with ischemic stroke without a history of diabetes mellitus in the ACROSS-China (Abnormal Glucose Regulation in Patients with Acute Stroke across China) registry were included. Stress hyperglycemia was measured by glucose-to-glycated hemoglobin (HbA1c) ratio. Glucose-to-HbA1c ratio were calculated by fasting plasma glucose divided by HbA1c and categorized into four even groups according to the quartiles. Outcomes included stroke recurrence and all-cause death at 12 months after stroke onset. Results A total of 999 patients were included, among which 105 (10.9%) recurrent stroke and 76 (7.6%) death occurred at 12 months. Compared with patients with the lowest quartile, patients with the highest quartile of glucose-to-HbA1c ratio was associated with an increased risk of stroke recurrence (16.0% vs. 8.3%; adj.hazards ratio [HR]= 2.19, 95% confidence interval [CI]: 1.26-3.83) and death (13.0% vs. 4.3%; adj.HR=2.86, 95%CI: 1.38-5.90) at 12 months after adjusted for potential covariates. Using Cox regression models with restricted cubic spline, we also observed higher level of glucose-to-HbA1c ratio was associated with an increased risk of stroke recurrence and death. Conclusion Stress hyperglycemia, measured by glucose-to-HbA1c ratio, was related to an elevated risk of 12-month stroke recurrence and death in nondiabetic patients with acute ischemic stroke.